The Implementation of SWOT Analysis in Managing Academic Quality in Public Elementary Schools in Toroh District - Himawan Eko Purnomo; Harjito Harjito; Maryanto Maryanto (Papanda Publisher, 2026)
This study investigates the implementation of SWOT analysis as a strategic management tool for academic quality improvement in public elementary schools in Toroh District, Grobogan Regency, Indonesia. Despite growing scholarship on SWOT applications in educational settings, its systematic use in academic quality management across multiple schools at the district level remains underexplored. Employing a qualitative descriptive approach with a multi-site case study design, data were collected from six school principals and twelve classroom teachers through semi-structured interviews, structured observations, and document analysis. Findings reveal that SWOT analysis effectively surfaced three primary internal strengths — teacher competence, principal leadership, and structured academic programs — alongside three persistent weaknesses: limited learning facilities, inconsistent instructional methods, and restricted professional development access. Externally, government educational support and community involvement were identified as key opportunities, while rapid policy change and inter-institutional competition constituted principal threats. Importantly, an informal peer-mentoring network operating outside formal structures was identified as an unrecognized latent strength. SWOT-based strategy formulation aligned internal capacities with external opportunities; however, a notable gap between strategic intent and operational specificity was observed in the WT quadrant. These findings reframe SWOT analysis as an organizational learning catalyst rather than a static diagnostic tool, offering theoretical and practical implications for evidence-based school improvement planning.